53.5k views
3 votes
Which could be the first step in simplifying this expression? Check all that apply. (x cubed x Superscript negative 6 Baseline) squared (x Superscript negative 18 Baseline) squared (x Superscript negative 3 Baseline) squared (x Superscript negative 2 Baseline) squared x Superscript 6 Baseline x Superscript negative 12 Baseline x Superscript 5 Baseline x Superscript negative 4. Need Help ASAP!

Which could be the first step in simplifying this expression? Check all that apply-example-1
User Eckstein
by
5.3k points

2 Answers

5 votes

Answer:

b d

Explanation:

User Peter Bennink
by
5.4k points
5 votes

Answer:


(x^(-3) )^(2)


x^6 x^(-12)

Explanation:


(x^(3) x^(-6) )^(2) is the expression given to be solved.

First of all let us have a look at 3 formulas:


1.\ p^a * p^b = p^((a+b))\\2.\ (p^a * q^b)^c = (p^(a))^c * (q^(b))^c\\3.\ (p^a)^b = p^(a* b)

Both the formula can be applied to the expression(
(x^(3) x^(-6) )^(2)) during the first step while solving it.

Applying formula (1):


(x^(3) x^(-6) )^(2)

Comparing the terms of
(x^(3) x^(-6) ) with
p^a * p^b


p=x, a =3, b=-6


\Rightarrow x^(3+(-6))\\\Rightarrow x^(3-6)\\\Rightarrow x^(-3)

So,
(x^(3) x^(-6) )^(2) is reduced to
(x^(-3) )^(2)

Applying formula (2):

Comparing the terms of
(x^(3) x^(-6) )^(2) with
(p^a * q^b)^c


p=q=x, a =3, b=-6, c=2


\Rightarrow (x^(3))^2* (x^(-6))^2\\\text{Applying Formula (3)}\\x^6 x^(-12)

So,
(x^(3) x^(-6) )^(2) is reduced to
x^6 x^(-12).

So, the answers can be:


(x^(-3) )^(2)


x^6 x^(-12)

User Marion
by
5.4k points